2004
DOI: 10.1055/s-2004-815727
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Measurement to Detect Medullary Thyroid Carcinoma in Nodular Goiter: German Evidence-Based Consensus Recommendation

Abstract: Serum calcitonin (CT) has become a very specific and sensitive marker for human medullary thyroid carcinoma (MTC), a neuroendocrine tumor affecting about 1 % of patients with nodular thyroid disease. MTC is characterized by early micrometastasis and a lack of curative non-surgical treatment, so that early diagnosis is desirable. Based on a systematic review of scientific evidence, we propose multidisciplinary consensus recommendations for the clinical use of CT in patients with nodular goiter. To exclude MTC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
33

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 33 publications
2
64
0
33
Order By: Relevance
“…This is in accordance with the upper limit of the normal range of 100 pg/dl, as published in the German consensus recommendation of 2004 (10). The recommended yearly follow-up investigations in patients with pentagastrin stimulation of hCT between 50 and 100 pg/dl can shed new light on this issue.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is in accordance with the upper limit of the normal range of 100 pg/dl, as published in the German consensus recommendation of 2004 (10). The recommended yearly follow-up investigations in patients with pentagastrin stimulation of hCT between 50 and 100 pg/dl can shed new light on this issue.…”
Section: Discussionsupporting
confidence: 85%
“…In spite of the fact that many European consensus groups and societies recommended hCT measurement as the screening parameter that detects medullary thyroid cancer, the majority of the physicians do not routinely use this test (10,11). In the last few years, several studies revealed different upper limits of basal hCT values to detect MTC and to reduce false-positive cases (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons underlying these disparate trends are unknown. In Europe, calcitonin screening of patients with thyroid nodules has been embraced with greater enthusiasm (30,31) than in the US, where it is not routinely recommended because of concerns regarding its cost-effectiveness (33,34).…”
Section: Trends Of Primary Tumor Size In Patients With Papillary and mentioning
confidence: 99%
“…This prompted the German Society for Endocrinology Thyroid Group in 2004 (11), followed by an interdisciplinary European consensus group in 2006 (12), to recommend calcitonin screening in patients with nodular thyroid disease. These recommendations have been greeted with less enthusiasm in some parts of the world because of lingering concerns regarding cost-effectiveness, prompting the revised American Thyroid Association guidelines to recommend neither for nor against the routine use of calcitonin screening in patients with nodular goiters (13).…”
Section: Introductionmentioning
confidence: 99%